Representing Evolutionary Theory in Nonfiction Picturebooks. Issue 2 (June 2022) - Tandoi, Eve; Spring, Erin
Abstract : This article asks how the theory of evolution is represented within nonfiction picturebooks. Twenty-eight picturebooks were originally identified through a series of online searches and crowdsourcing exercises. In this article we look closely at a handful of examples that lend themselves to discussing how nonfiction picturebooks manage readers' expectations, translate science through their use of metaphors, and encourage readers to engage with alternative perspectives.